PADRÕES DE PRODUTIVIDADE EM PESQUISA NA LITERATURA DE FINANÇAS: UM ESTUDO BIBLIOMÉTRICO NOS PRINCIPAIS PERIÓDICOS CIENTÍFICOS NACIONAIS NO PERÍODO DE 2005 A 2014 - CANDIDO, RICARDO BATISTA (2015)
The Financial Administration comes in the early XIX century with the movement of consolidation of big business and the formation of the American national markets while in Brazil the first studies occur from the second half of the XX century. Since then the country has managed to consolidate some centers of excellence in research, form significant group of senior researchers and expand the areas of research in the field, however, there are few studies that seek to portray the characteristics of scientific productivity in Finance. Seeking to contribute to a better understanding of production behavior of this area this research studies its scientific production, materialized in the form of digital articles published in 24 national journals highly ranked in the strata Qualis / CAPES A2, B1 and B2 of the Administration Area, Accounting and Tourism. For both are applied to Bradford's Law, Elitism Act of Price and Lotka's Law. By Bradford Act identifies three productivity areas and the core consists of three magazines, one of them being classified in stratum Qualis / CAPES B2, which highlights the limitation of a cut on the sole criterion to Qualis / CAPES classification. For Elitism Act of Price, either by direct or full count, did not identify the behavior of an elite similar to that indicated by the theory and which has large number of authors with one publication. Applying the model of Inverse Power Generalized calculated by Ordinary Least Squares (OLS), we found that productivity of researchers, when done by direct counting, suited to that defined by the Lotka Law to the level of α = 0.01 significance, however, the complete count can not confirm the hypothesis of homogeneity of the distributions, plus the fact that the two counts productivity analyzed by the parameter n is greater than 2 and therefore the productivity of the finance researchers is lower than that advocated by the theory .